Mindfulness-Based Approaches to Addiction Prevention and Treatment for Children and Adolescents: Thematic Background and Overview of the Ongoing IMAC-Mind Network Achtsamkeitsorientierte Ansätze der Suchtprävention und -therapie bei Kindern und Jugendlichen Thematischer Hintergrund und Überblick zu dem laufenden IMAC-Mind Verbund - Arnaud, Nicolas; Banaschewski, Tobias; Nees, Frauke; Buchholz, Verena Nadine; Klein, Michael; Reis, Olaf; Legenbauer, Tanja; Zapf, Antonia; Thomasius, Rainer (Sucht, 2022)
Background: Adolescence is considered a vulnerable phase for the development of addictive disorders, with a large proportion of young people who is affected. Central for addictive behavior are problems in the executive control and self-regulation of feelings, thoughts and behavior. For years the concept of mindfulness has been in public focus. Numerous neurobiological and clinical studies demonstrate the benefi ts of mindfulness-based interventions for strengthening executive regulation of stress and behavioral impulses in addictive disorders and comorbid psychological symptoms. Methods: Selective literature review on mindfulness and substance-related disorders in children and adolescents. Results: Empirical evidence to assess the utility of mindfulness programs to prevent and treat addictive disorders in children and adolescents is lacking to date. As part of the ongoing research network "IMAC-Mind: Improving Mental Health and Reducing Addiction Risk in Childhood and Adolescence through Mindfulness: Mechanisms, Prevention, and Treatment," the multivariate risk profi les for addictive disorders are being investigated and translated into mindfulness-based intervention models. Conclusion: This article derives research needs on addictive disorders and mindfulness from a youth-specifi c perspective and provides information about ongoing projects in the research network.
CRIS-Team Scopus Importer:2022-03-04
Keywords: children and adolescents; mindfulness; prevention; self-regulation; substance use disorder; therapy